High prevalence of fasciolosis and evaluation of the efficacy of anthelmintics against Fasciola hepatica in buffaloes in Guangxi, China. (April 2019) - Zhang, Ji-Li; Si, Hong-Fei; Zhou, Xu-Zheng; Shang, Xiao-Fei; Li, Bing; Zhang, Ji-Yu
Abstract: Fasciola hepatica is a common parasite of grazing livestock in Guangxi Zhuang Autonomous Region in China, but its prevalence has not been studied. While triclabendazole is commonly used to treat F. hepatica infection in China, oxyclozanide has never been used. This study investigated the prevalence of F. hepatica infections in buffaloes in the Guangxi and evaluated the efficacy of oxyclozanide and triclabendazole as treatments. In the prevalence study, a total of 767 individual faecal samples were obtained from 58 farms in Guangxi to detect the prevalence of F. hepatica, and the total rate of infection was 87.35%. A subset of 277 infected buffaloes from these farms were randomly divided into 3 groups. Group 1 (n = 101) was treated with oxyclozanide at 10 mg/kg.bw; group 2 (n = 94) was treated with triclabendazole (12 mg/kg.bw); and group 3 (n = 82) was untreated. Faecal samples were taken on days 0, 7, 14, 21 and 28. Whole blood and serum were collected on days 0 and 14. Anthelmintic efficacy was assessed using faecal egg count reduction (FECR), buffaloes positive by coprology reduction (BPCR) as well as post-treatment improvement in biochemical and haematological indicators. After 28 days treatment, group 1 and 2 showed FECR% values above 98%, and BPCR% values of 97.03% and 77.66%, respectively. In addition, the biochemical indicators and haematological parameters were improved at 14 days post-treatment compared with those before treatment. These results indicate a high prevalence of F. hepatica in Guangxi, demonstrate that oxyclozanide and triclabendazole are effective against F. hepatica infection in buffaloes, and indicate that oxyclozanide could be used in China as an alternative drug. Graphical abstract: Image 1 Highlights: The prevalence of F. hepatica infections in 767 buffaloes was 87.35% on 58 farms from 8 districts in Guangxi Zhuang Autonomous Region in China. Oxyclozanide and triclabendazole effectively restored the health of infected buffaloes and reduced the EPG of F. hepatica.